INNOCENCE, FANTASY, AND DANGER: THE HISTORICAL MEMORY OF THE SPANISH CIVIL WAR THROUGH THE LENS OF CHILDHOOD CURIOSITY - Escobar-Rivera , Luc (Young Scholars Grinchenko – Seton International Journal, 2026)
This article examines how Spanish cinema engages with the contested historical memory of the Spanish Civil War (1936-39) and the subsequent dictatorship of Francisco Franco (1939-1975) through the lens of childhood, fantasy, and curiosity. Focusing on Erice’s El espíritu de la colmena (The Spirit of the Beehive), Del Toro’s El espinazo del diablo (The Devil’s Backbone), and El laberinto del fauno (Pan’s Labyrinth), the paper argues that child protagonists, detached from any political ideology, offer a powerful narrative framework for exploring trauma, repression, and moral resistance. Their encounters with supernatural or imagined worlds contrast sharply with the violent realities of war and dictatorship, highlighting both the persistence of innocence and its vulnerability. The analysis situates these films within broader debates over Spain’s historical memory, including the legacy of silence following Franco’s regime and the delayed institutional recognition of its victims through Spain’s 2007 law of Historical Memory (Ley de Memoria Histórica). It demonstrates how filmmakers employ fantasy, allegory, and symbolism to circumvent censorship (in Erice's case) or to reach global audiences through visually rich storytelling (in del Toro's case), while consistently humanizing victims of repression, particularly Republican resistance fighters. Ultimately, the article contends that childhood curiosity operates as both a narrative device and a moral compass, allowing these films to reframe historical violence through empathy, wonder, and confrontation with danger. By juxtaposing innocence with brutality, these works challenge the culture of forgetting and assert the necessity of remembrance, suggesting that children's imaginative resilience symbolizes an enduring resistance to authoritarian erasure and a commitment to preserving historical truth.